Periodic ripples on thermally-annealed graphene on Cu (110)—reconstruction or moiré pattern?. (10th September 2018) - Durkan, Colm
Abstract: We have used ultrahigh vacuum scanning tunneling microscopy (STM) to investigate the effect of thermal annealing of graphene grown by chemical vapor deposition on a Cu(110) foil. We show that the annealing appears to induce a reconstruction of the Cu surface along the [210] direction, with a period of 1.43 nm. Such reconstructions have been ascribed to the tensile strain induced in the Cu surface by its differential thermal expansion relative to the graphene over-layer, but we show that it is in fact a moiré pattern due to interference between the graphene and the underlying atomic lattice as evidenced by the appearance of an odd–even transition only observed due to misorientation of the top layer of a layered crystal. This highlights that the analysis of STM measurements of graphene on metal surfaces should take such interference effects into account and that the graphene–Cu interface is more complex than previously thought.